The Role of the Algerian Legislator in Combating Discrimination and Hate Speech through Law 05-20 - Lomri, Mounir; Ghehioueche, Alwalid (Journal of Legal Studies and Researches, 2026)
In this study, we examine the role of the Algerian legislator in addressing the crime of discrimination and hate speech, both of which have witnessed a noticeable increase in recent times within Algerian society. The legislator took the initiative to enact Law No. 20-05, which includes a precise definition of the crimes of discrimination and hate speech, in addition to introducing a set of mechanisms to combat them. The law adopts a comprehensive approach based on two aspects: a preventive aspect that involves organizing awareness and sensitization campaigns to promote a culture of tolerance and reject hatred, and a punitive aspect that includes both principal and supplementary penalties aimed at reducing the commission of such acts and punishing their perpetrators.